1988
DOI: 10.1002/mrm.1910070406
|View full text |Cite
|
Sign up to set email alerts
|

Water proton NMR relaxation mechanisms in lung tissue

Abstract: The NMR relaxation times T'2, T2, and T1 were measured in isolated rat lungs as functions of external magnetic field B0, temperature, and lung inflation. The observed linear dependence on B0 of the tissue-induced free induction decay rate (T'2)-1 provides independent confirmation of the air/water interface model of the lung. Furthermore, measurements of the Larmor frequency dependence of T1 are consistent with a spin-lattice relaxation rate of the form 1/T1 = A omega -1/2 + B as expected for the case in which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

1991
1991
1999
1999

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 11 publications
3
38
0
Order By: Relevance
“…Proton relaxation times of compartmentalized water have been determined in tissues (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15), gels (22)(23)(24)(25), food materials ( 2 6 ) , and plants (27). In general, a monoexponential relaxation process of water in a closed compartment indicates fast exchange between free water and hydration water according to and h relate to free and hydration water.…”
Section: Efective Relaxation Mechanisms In Gelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Proton relaxation times of compartmentalized water have been determined in tissues (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15), gels (22)(23)(24)(25), food materials ( 2 6 ) , and plants (27). In general, a monoexponential relaxation process of water in a closed compartment indicates fast exchange between free water and hydration water according to and h relate to free and hydration water.…”
Section: Efective Relaxation Mechanisms In Gelsmentioning
confidence: 99%
“…More accurate measurements and a better analysis of relaxation processes (in vitro and in vivo) should be based on a large number of data points of a relaxation curve allowing the decomposition of multiexponential processes into monoexponential components. These monoexponential components may be more useful for the improved determination of TI and T 2 and allow the estimation of fractions of the relaxation components in each voxel, which correlate with the proton density of a particular water fraction (7)(8)(9)(10). However, it should not be withheld that it is difficult to obtain well-digitized relaxation curves employing routine imaging procedures and that one needs special techniques ( 12).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Proton MRI studies have demonstrated correlation of the signal intensity from edematous lungs with the amount of lung water present (6)(7)(8)(9)(10). Proton lung water imaging, though, is complicated by magnetic susceptibility effects (11,12). Further, protons in all the fluid compartments of the edematous lungs-intracellular, alveolar, interstitial, and plasma-contribute to the total signal intensity.…”
Section: Introductionmentioning
confidence: 98%
“…The resulting susceptibility gradients at the air/tissue interfaces are the cause of the short relaxation times, with T 2 * being of the order of 0.5-1 ms, while T 2 shows a biexponential decay with a short component of 1 ms and a longer one of 50-100 ms, respectively. 225,226 These factors largely prevent the detection of signals from lung parenchyma using conventional spin-echo or gradient-echo pulse sequences. Moreover, cardiac and respiratory motion as well as pulsatile blood flow in the thoracic vasculature render MRI of the lung difficult.…”
Section: Other Applications In Drug Developmentmentioning
confidence: 99%